Anne of the island - Montgomery, L.M. (Watermill press, 1994)
Anne Shirley has come a long way since her days as a mischievous orphan living in the house at Green Gables. She is now eighteen and headed to faraway Redmond College in Kingsport. Anne's college years are sure to be full of fun, but they will also be a time for soul-searching and big decisions.